Kult archaniołów w późnej starożytności – wybrane zagadnienia - Adamiak, Stanisław (Vox Patrum, 2023)
The article presents selected testimonies of the cult of archangels in Late Antiquity. The accounts of martyrdom and various inscriptions are analysed, primarily from North Africa, Asia Minor, Egypt and Nubia. They have been taken mainly from the “Cult of Saints in Late Antiquity” database. Examples of both orthodox and syncretistic piety invoking the intercession of archangels are shown. The special role of the Archangel Michael has been underlined. Considerations on the admissibility of depicting angels in the Christian art of Late Antiquity are also presented.